Sex-ratio and body size plasticity in two cold-adapted ground beetles co-occurring in a periglacial area of the European Alps (Coleoptera: Carabidae) - Ornaghi, Simone; Valle, Barbara; Caccianiga, Marco; Seppi, Roberto; Gobbi, Mauro (Fragmenta entomologica, 2023)
Differences in the sex-ratio and morphometric parameters in cold-adapted ground beetles were analysed to investigate environmental heterogeneity at small scale in a periglacial contest of the European Alps. Four hundred and thirty specimens of two cold-adapted ground beetles – Nebria germarii (Heer, 1837) and Nebria castanea (Bonelli 1810) – were analysed in order to test the presence of variation in sex-ratio, sexual dimorphism and morphometric parameters in relation to the occurrence of ice, and other environmental variables. Specifically, the populations found on an ice-related landform (active rock glacier) were compared with those on ice-free landforms (a fossil rock glacier and a scree slope). Both species experience sex-dependent morphometric plasticity. In addition, sex-ratio is female-biased,supporting female pioneering tendency in all the studied landforms. Two morphometric parameters resulted indirectly affected by the presence/absence of ice in the terrain: the head width decreases, while elytra width increases passing from ice-free to ice-related landform. Both these morphometric differences may be related to the increase of intra/interspecific competition and to the lower trophic availability. This study highlights that even if these high altitude cold-adapted species are able to survive on ice-free landforms, they probably find more favourable conditions on ice-related landforms. Since the two species show different sensitivity to the ice-presence, it is not always possible to detect this preference through abundances variability (e.g for N. castanea), but it necessary to use more detailed morphometric analysis. Head width and elytra width are good candidates as response traits of interstitial ice occurrence in stony terrains.